A Polymorphism of ORAI1 rs7135617, Is Associated with Susceptibility to Rheumatoid Arthritis. (7th April 2014) - Yen, Jeng-Hsien; Chang, Che-Mai; Hsu, Yu-Wen; Lee, Chih-Hung; Wu, Mei-Shin; Hwang, Daw-Yang; Chen, Ben-Kuen; Liao, Hsien-Tzung; Wu, Man-Tzu Marcie; Chang, Wei-Chiao
Abstract : Rheumatoid arthritis (RA), a chronic inflammatory disease usually occurring in synovial tissues and joints, is highly associated with genetic and environmental factors. ORAI1, a gene related to cellular immune system, has been shown to be involved in the pathogenesis of chronic inflammatory diseases and immune diseases. To identify whether ORAI1 gene contributes to RA susceptibility, we enrolled 400 patients with RA and 621 healthy individuals for a case-control genetic association study. Five tagging single nucleotides polymorphisms (tSPNs) within ORAI1 gene were selected for genotyping. An SNP, rs7135617, showed a significant correlation with the risk of RA. Our results indicated that genetic polymorphism of ORAI1 gene is involved in the susceptibility of RA in a Taiwanese population.